Climate Change and the Impact on Ocular Infectious Diseases: A Narrative Review - Yong Le Tong; Carlos Cifuentes-González; Kajal Agrawal; Fatma Shakarchi; Xin Ying Rachel Song; John S. Ji; Rupesh Agrawal (Ophthalmology and Therapy)
Abstract Climate change and global warming significantly affect the incidence and distribution of infectious ocular diseases. This narrative review explores how climate-related factors—including extreme weather events, precipitation, temperature fluctuations, humidity, wind patterns, ultraviolet radiation, and air pollution—can directly and indirectly influence the burden of ocular infections. By synthesizing evidence from the published literature, we examine how these environmental variables impact disease mechanisms such as pathogen survival, transmission dynamics, and host susceptibility. Increased precipitation has been associated with a higher incidence and recurrence of ocular toxoplasmosis (OT), likely due to the enhanced spread of Toxoplasma gondii oocysts through contaminated water and soil. Rainfall also creates breeding habitats for mosquitoes, facilitating the transmission of vector-borne diseases such as dengue fever and Rift Valley fever. Rising temperatures and humidity have been linked to increased rates of fungal infections, particularly fungal keratitis in tropical regions. Wind has been implicated in the airborne dispersal of pathogens, including fungal spores, T. gondii oocysts, and insect-derived particles such as moth setae, potentially contributing to OT and seasonal hyperacute panuveitis. Air pollution further exacerbates dry eye disease, which influences the vulnerability to microbial keratitis. These climate-related shifts disproportionately affect vulnerable populations—particularly those living in rural, low-income, and tropical areas. This review highlights the urgent need for further research into climate-sensitive mechanisms of ocular infections and the development of targeted adaptation strategies to mitigate their impact on global eye health.